Obtaining Responses to Sensitive Questions: Conventional Questionnaire versus Randomized Response Technique - Buchman, Thomas A.; Tracy, John A. (Journal of Accounting Research, 1982)
Thomas A. Buchman, John A. Tracy, Obtaining Responses to Sensitive Questions: Conventional Questionnaire versus Randomized Response Technique, Journal of Accounting Research, Vol. 20, No. 1 (Spring, 1982), pp. 263-271